Does value chain integration dampen producer price developments? Evidence from the European Union - Klaus S. Friesenbichler; Agnes Kügler; Andreas Reinstaller (Austrian Institute of Economic Research (WIFO), 2020)
We draw on trade theory to empirically explore the effects of value chain integration on producer price dynamics. Using the EU as an example of an integrated area, we construct measures of backward and forward linkages with intra- and extra-EU trading partners at the country-sector level. We find that especially upstream integration and EU-accession dampen inflation. The results for downstream integration indicate a price-increasing relationship. We propose novel EU integration indicators and offer insights to both theory and applied research. We also add to the policy debate on the price effects of (dis-)integration of EU countries.
Keywords: E31; F15; O52; 330; inflation; EU integration; Single Market; producer prices; value chains